State building in revolutionary Ukraine : a comparative study of governments and bureaucrats, 1917-1922 - Velychenko, Stephen (Book collections on Project MUSE., 2011)
"State Building in Revolutionary Ukraine examines six attempts to create governments on Ukrainian territories between 1917 and 1922. Focusing on how political leaders formed and staffed administrations, this study shows that in Ukraine during this time, there was an available pool of able administrators sufficiently competent in Ukrainian to work as bureaucrats in the independent national governments. These people could sometimes implement policies, a significant accomplishment in light of the upheavals of the time.